Tax Avoidance of Mining Sector Companies Registered on The Indonesia Stock Exchange - Melisa Dwi Kirnanda; Trisni Suryarini; Nur Anita (UNIB Press, 2024)
This study aims to test and analyze the effect of deferred tax burden, thin capitalization, and financial distress on tax avoidance with managerial ownership as a moderating variable. It uses a quantitative approach. The population is mining companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique uses purposive sampling, which produces a sample of 73 analysis units. Data collection uses documentation techniques. Data analysis uses panel data regression and moderated regression analysis (MRA) with the Eviews 12 program as the analysis tool. The results of this study indicate that deferred tax burden does not affect tax avoidance; thin capitalization negatively affects tax avoidance, while financial distress positively impacts tax avoidance. Managerial ownership cannot moderate the effect of deferred tax burden and financial distress on tax avoidance. Managerial ownership can weaken the impact of thin capitalization on tax avoidance. The novelty is adding the deferred tax burden variable as an independent variable and choosing managerial ownership as a moderating variable. The financial distress variable is measured using the springate model.